2021
DOI: 10.1038/s41390-020-01306-4
|View full text |Cite
|
Sign up to set email alerts
|

Continuous chest compressions with asynchronous ventilations increase carotid blood flow in the perinatal asphyxiated lamb model

Abstract: BACKGROUND:The neonatal resuscitation program (NRP) recommends interrupted chest compressions (CCs) with ventilation in the severely bradycardic neonate. The conventional 3:1 compression-to-ventilation (C:V) resuscitation provides 90 CCs/min, significantly lower than the intrinsic newborn heart rate (120-160 beats/min). Continuous CC with asynchronous ventilation (CCCaV) may improve the success of return of spontaneous circulation (ROSC). METHODS: Twenty-two near-term fetal lambs were randomized to interrupted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The duration of CPR associated with successful ROSC using an endotracheal tube as the airway device reported from similar experimental protocols in lambs was reviewed. The median(IQR) time to ROSC reported in a couple of recently published similar animal protocols from our lab was 8 min (6.3 – 10) and 6.1 min (2.9 −7.1) 22 , 23 Based on the review of published work from our lab, we calculated the standard deviation of the time to ROSC(outcome) in the control group (comparator) as 3 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The duration of CPR associated with successful ROSC using an endotracheal tube as the airway device reported from similar experimental protocols in lambs was reviewed. The median(IQR) time to ROSC reported in a couple of recently published similar animal protocols from our lab was 8 min (6.3 – 10) and 6.1 min (2.9 −7.1) 22 , 23 Based on the review of published work from our lab, we calculated the standard deviation of the time to ROSC(outcome) in the control group (comparator) as 3 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…17 23 24 29 However, Aggelina et al reported significant improvement in survival (70% vs 20%, p=0.02), time to ROSC (median (IQR) 60 (60–60) vs 30 (30–30) s, p=0.02) and coronary perfusion pressure (mean (SD) 45.7 (16.9) vs 21.8 (6) mm Hg, p<0.001) in 1–4-day-old asphyxiated piglets resuscitated using CCaV compared with 3:1 C:V (table 1). 32 Further, Vali et al reported significant higher PaO 2 (partial oxygen tension) (22 (5.3) vs 15 (3.5) mm Hg, p<0.01), left carotid blood flow (7.5 (3.1) vs 4.3 (2.6) mL/kg/min, p<0.01) and oxygen delivery (0.40 (0.15) vs 0.13 (0.07) mL O 2 /kg/min, p<0.01) using CCaV compared with 3:1 C:V 33. Manikin studies reported that CCaV compared with 3:1 C:V resulted in decreased CC depth over time,13–15 lower tidal volume,12 15 a higher minute ventilation,12 15 as well as greater rescuers’ physical fatigue13 14 (table 1).…”
Section: Resultsmentioning
confidence: 93%
“…In manikins, CCaV compared with 3:1 C:V ratio increased fatigue (table 1). One animal study comparing CCaV and 3:1 C:V ratio reported significant carotid blood flow and cerebral oxygen delivery,33 and another animal study reported significant improvement in time to ROSC and survival in piglets resuscitated with CCaV;32 other studies reported no difference in time to ROSC and survival (table 1). 17 18 23 24…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the piglets in the 90/min and 100/min groups had higher cerebral inflammation and brain injury than those in the 120/min group [ 23 ]. Similar, Vali et al [ 24 ] used a transitional asphyxia lamb model and randomized them to either 3:1 C:V (90 CCs + 30 breaths/min) or continuous CC with asynchronized ventilation with CC rate of (120 CCs + 30 breaths/min) and reported no difference in rate of and time to ROSC. Continuous CC with asynchronized ventilation was associated with a higher PaO 2 , greater left carotid blood flow, and oxygen delivery.…”
Section: Discussionmentioning
confidence: 99%